Metallogenic Dynamics Background of Ga’erqiong Cu-Au Deposit in Tibet, China - Ouyang, Yuan; Yang, Wunian; Huang, Hanxiao; Liu, Hong; Zhang, Jianlong; Zhang, Jianhua (Earth Sciences Research Journal, 2017)
The Ga’erqiong Cu-Au deposit, which sits on the north side of the Coqên-Xainzamagmatite belt, is a large-scale skarn-type deposit, whose ore body has formed in the skarn zone in the contact part of quartz diorite and marble of Duoai formation or the cracks of quartz diorite. Its mineralization is closely related to quartz diorite. And granite porphyry-related molybdenum ore still exists in its deep part. Currently, there are disputes about the metallogenic dynamics background of this deposit. From previous studies, this paper carried out zircon LA-LCPMS U-Pb dating and petrogeochemistry study for quartz diorite of Ga’erqiong Cu-Au deposit. The testing result indicates: quartz diorite and granite porphyry were formed respectively in 88±2Ma and 83±1Ma, belonging to the magmatic activity of the early stage of Upper Cretaceous; quartz diorite and granite porphyry have geochemical characteristics similar to those of island arc rock of subduction zone and geochemical indexes similar to “adakite.” Combining with the regional tectonic evolution, we think that quartz diorite and granite porphyry were all formed in the extension environment after the collision of Lhasa block and Qiangtang block. Quartz diorite is the result of the migmatization of basic melt and acid melt evoked by asthenosphere material raise caused by lower crustal delamination; the formation of granite porphyry may be crust-mantle material’s partial melting results due to delaminated lower crustal. Therefore, Ga’erqiongskarn-type Cu-Au deposit belongs to the metallogenic response to the collisional orogeny in the closing process of Meso-Tethys.